Melacak Akar Wasaṭiyyah Dalam Hadis Nabi SAW - Budiman, Arif; Karni, Awis; Ashadi, Andri; Sari, Fitri (Moderatio: Jurnal Moderasi Beragama, 2023)
This article discusses the traces of wasaṭiyyah in the Prophet's hadith narratives. Specifically, it explores the events of the Medina Charter which can be used as a symbol of wasaṭiyah in the history of Muslims. The discourse of religious moderation has normatively been displayed in the narrative and behavior of the Prophet SAW. With a narrative research model, this research traces the events into a single unit so that the correlation of existing events is obtained. As a result, the search for hadith with the keyword ummatan wasaṭan is found in several collections of canonical books scattered in four books totaling 10 hadith. These traditions are closely related to the interpretation of QS. Al-Baqarah [2]: 143. Second, in principle, there is a symbolic meaning of wasaṭiyyah in other hadith reports that substantively show the practice reflected by the Prophet SAW who was fair, polite, able to tolerate differences. In addition, the discussion of the Medina Charter is realized on the basis of spiritual, economic and socio-political integration with four significances (a) this charter represents the recognition of ethnic Jews as a people in the sense of their religious freedom, meaning that there is a principle of tolerance. (b) The obligation on the Jews to share the costs with the Muslims in the event of an attack from outside Medina and the recognition of the Jewish side of the Prophet's supreme authority in all disputes between the parties, this principle indicates a commitment to nationality (c) the establishment of restrictions on the movement of Jews outside Medina except with the permission of the Prophet and (d) the establishment of Medina's territory that is free of disputes and destruction of its natural resources which shows the principle of non-violence. Clearly, the roots of wasatiyyah in the prophetic narrative always prioritize religious tolerance without disputes and disputes.